40.9k views
1 vote
I just want to know if I solved it right before I turn it in

I just want to know if I solved it right before I turn it in-example-1
User Porshia
by
4.7k points

1 Answer

6 votes

Solving for x in the second equation, we get:


\begin{gathered} -3x+4y=-13 \\ -3x=-13-4y \\ x=(-13)/(-3)-(4y)/((-3)) \\ x=(13)/(3)+(4y)/(3) \end{gathered}

Replacing x on the first one and solving for y, we get:


\begin{gathered} 2x+5y=1 \\ 2((13)/(3)+(4y)/(3))+5y=1 \\ (26)/(3)+(8y)/(3)+5y=1 \\ (8y)/(3)+5y=1-(26)/(3) \\ (23)/(3)y=(-23)/(3) \\ y=-1 \end{gathered}

Finally, replacing y by -1, we get:


\begin{gathered} x=(13)/(3)+(4)/(3)\cdot(-1) \\ x=(13)/(3)-(4)/(3) \\ x=3 \end{gathered}

Answer: x = 3 and y = -1

User Jory Geerts
by
4.6k points